Vascular reconstructions in living donor kidney transplantation: a single-center experience over the last 17 years - Roth, Nadina; Kalteis, Manfred; Krause, Axel; Rösch, Christiane Sophie; Huber, Jürgen; Enkner, Wolfgang; Haller, Maria; Cejka, Daniel; Függer, Reinhold; Biebl, Matthias (Frontiers in Transplantation, 2024)
IntroductionIn living donor kidney transplantation (LDKT), vascular anastomosis is more difficult due to missing arterial patches and shorter renal veins. The surgical challenge is even more demanding in kidneys with multiple arteries. Although renal transplantation is feasible in most cases of complex donor vascular anatomy and similar results compared with standard LDKT are reported, the discussion on potentially increased complication rates and graft function continues. This prompted us to review our results of LDKT with multiple renal artery (MRA) grafts with a special concentration on complications and long-term function.Patients and methodsWe reviewed the records of all LDKT in our center from the beginning of the program in 2005 until 2022 for arterial vascular reconstructions. The cohort was divided into two groups: transplantation with vascular reconstruction (VR) and standard transplantation. These groups were compared for operative parameters and short- and long-term results.ResultsFrom 2005 to 2022, 211 LDKT were completed in our unit. In 32 (15.2%), a VR was performed, including single ostium side-to-side anastomosis, end-to-side anastomosis, patch reconstruction, and vein interposition. There was no significant difference in operative time (169 min vs. 180 min; p = 0.118) and time for anastomosis (28 min vs. 26 min; p = 0.59) between both groups. Postoperative complications (5.7% vs. 7.4%; p = 0.72) were not significantly different. During the follow-up period (110 months, range 10–204), the risk of organ loss was comparable after VR (13.625% vs. 11.56% p = 0.69).ConclusionIn LDKT, arterial vascular reconstructions for kidneys with MRA provide similar results compared to grafts with a single renal artery (SRA). Short- and long-term results are comparable with standard procedures.